Comprehensive profiling of serum microRNAs in normal and non-alcoholic fatty liver disease (NAFLD) patients - Jian-Wei Zhang; Kamran Ullah; Nauman Khan; Hai-Tao Pan (Scientific Reports)
Abstract Pediatric non-alcoholic fatty liver disease (NAFLD) is emerging as a worldwide health concern with the potential to advance to cirrhosis and liver cancer. NAFLD can also directly contribute to heart problems through inflammation and insulin resistance, even in individuals without other risk factors. The pathological mechanisms of NAFLD are linked to functional differences of miRNAs in different biological environments. The miRNA in serum exosomes may reflect the pathological state of the liver and changes in systemic metabolism, while the miRNA in serum may be associated with physiological processes other than the liver. Pediatric non-alcoholic fatty liver disease (NAFLD) is emerging as a worldwide health concern with the potential to advance to cirrhosis and liver cancer. NAFLD can also directly contribute to heart problems through inflammation and insulin resistance, even in individuals without other risk factors. The pathological mechanisms of NAFLD are linked to functional differences of miRNAs in different biological environments. The miRNA in serum exosomes may reflect the pathological state of the liver and changes in systemic metabolism, while the miRNA in serum may be associated with physiological processes other than the liver. Pediatric non-alcoholic fatty liver disease (NAFLD) is emerging as a worldwide health concern with the potential to advance to cirrhosis and liver cancer. NAFLD can also directly contribute to heart problems through inflammation and insulin resistance, even in individuals without other risk factors. The pathological mechanisms of NAFLD are linked to functional differences of miRNAs in different biological environments. The miRNA in serum exosomes may reflect the pathological state of the liver and changes in systemic metabolism, while the miRNA in serum may be associated with physiological processes other than the liver. Our study identified 36 miRNAs with differential expression in the serum of NAFLD patients compared to the control group, including 21 miRNAs with significantly increased expression and 15 with decreased expression. Consistent with our previously reported data on serum-derived exosomal miRNA profiling, this study also observed a notable upregulation of serum miR-122-5p levels in NAFLD patients. PCR validation confirmed the differential expression of miR-122-5p identified through RNA sequencing. Functional analysis using GO and KEGG pathways revealed a diverse range of biological roles associated with these differentially expressed miRNAs. Notably, NAFLD significantly impacts heart health, with miR-122-5p playing a key role in regulating cardiovascular function. Furthermore, activation of the miR-122/Sirt-6/ACE2 axis may contribute to myocardial necrosis, highlighting its potential role in NAFLD-associated cardiovascular risks. Our study suggests that miR-122 plays a key role in the progression of NAFLD and its associated metabolic disturbances, which can increase the risk of cardiovascular disease. Targeting miR-122 may offer potential therapeutic benefits for improving both liver and heart health in individuals with NAFLD.